Foreign direct investment and income inequality: Evidence from developing economies - Obradović Saša; Lojanica Nemanja (Anali Ekonomskog fakulteta u Subotici, 2015)
The primary aim of this paper is to determine the impact of foreign direct investment on income inequality distribution. The main hypothesis of the paper is that an increase in the inflow of the foreign direct investment in developing countries leads to a reduction in income inequality. From global perspective, there is an increasing economic inequality, if we look at it through the participation of the richest and poorest population in total income for given economy. On the other hand, emerging economies become increasingly important participants in the movement of foreign direct investment, primarily as a popular destination. Therefore, using regression analysis, the paper aims at examining whether there is a statistically significant correlation between economic inequality and the inflow of foreign direct investment.